Transformation of hazardous zinc sludge into highly porous spinel/whisker-form mullite membranes for the separation of oil-in-water emulsions. Issue 11 (September 2022) - Li, Lingling; Huang, Dexuan; Gao, Zixiang; Cao, Gengyu; Zhao, Ruiming; Ma, Hao; Li, Xiang; Li, Ning; Zhang, Aiyu
Abstract: Heavy metal waste poses an environmental and health hazard. Zinc-containing sludge is a particular problem. However, the conversion of this sludge into a spinel-based ceramic material is an environmentally friendly, space-saving, and cost-effective method for preventing heavy-metal pollution. However, silicates are frequently present in such sludge, and can reduce the porosity of the produce ceramic material, which limits their potential applications in membrane-separation technology. To ensure the conversion of the zinc component into a highly porous spinel-based ceramic, in this study, additives were used to convert the silica component to whisker-form mullite. Thus, a primary pore structure was formed between spinel particles, and secondary pore channels were formed by the mullite whiskers in the primary pores. Crucially, the oriented growth of a ceramic containing 15% ZnO at 1150 °C resulted in a porosity of 40.5%. In contrast, the unmodified ceramic had a porosity of 6.3%. The unique structure also reduced the tortuosity of the ceramic to less than unity, which improved the permeation flux for membrane applications. The optimal ceramic was tested for the separation of oil-in-water emulsions, yielding a promising oil-rejection rate of 96%.